The Overview of the Condition of Student Learning Burnout Behavior in Senior High School Level - Darmuji, Nita Wulan Sari; Fitriana, Siti; Sativi, Andarini Bhakti (IKIP Siliwangi, 2024)
Learning Burnout Behavior is a condition where a person mentally experiences learning saturation, resulting in students experiencing a loss of motivation to learn. This background is done by the author because of the existence of learning burnout behavior. Researchers conducted this study to determine the level of learning burnout behavior of class XI students at SMA Negeri Semarang. The research method used descriptive quantitative research with observational descriptive research conducted on class XI students with a simple random sampling technique. The results of this study indicate that students from 108 students of class XI SMA Negeri 11 Semarang are in a high position with a percentage of 55% with 59 students and a low percentage of 45% with 49%. This result shows that the students of class XI SMA Negeri 11 Semarang are in a high position